Tourism Growth from Environmental Degradation: A Sound Governance Approach to Sustainable Destination Manage-ment and SDG Integration - Dina Daniati; Diane Laurentia; Tantie Aqsha; Apri Kuntariningsih; Lidya Fitri Yani (An International Journal Tourism and Community Review, 2026)
This research investigates the integration of Sound Governance principles within the sustainable tourism policy cycle as a mechanism to mitigate institutional fragmentation and evaluation inefficiencies in developing economies. Adopting a sequential explanatory mixed-methods design, the study establishes a multidimensional evaluation framework congruent with the Sustainable Development Goals (SDGs). Policy performance is rigorously analyzed across five strategic domains: Economy, Social-Welfare, Culture-Education, Environment, and Governance. The quantitative methodology employs 17 adapted SDG indicators to assess policy efficacy, while the subsequent qualitative phase utilizes semi-structured interviews and stakeholder mapping to deconstruct complex power dynamics within multi-actor co-management structures. The empirical findings demonstrate that Sound Governance—predicated on transparency and accountability—acts as a fundamental catalyst for policy effectiveness. It significantly enhances destination sustainability through a structured input-process-output-outcome-impact pathway. Evidence from the case study of Penglipuran Village, Bali, validates these results, showing that while indigenous institutional legitimacy bolsters social responsiveness, it remains susceptible to economic dependencies driven by overtourism. Ultimately, this study asserts that embedding SDGs into the policy evaluation cycle elevates assessments from perfunctory administrative exercises to strategic instruments essential for ecosystem preservation and long-term demand stability. These insights establish Sound Governance as a strategic intangible asset, providing significant theoretical contributions to development administration and offering pragmatic frameworks for policy-makers managing sustainable destinations in competitive global markets.